The heroes - Abercrombie, Joe (London : Gollancz, 2012)
Over three bloody days of battle, the fate of the North will be decided. But with both sides riddled by intrigues, follies, feuds and petty jealousies, it is unlikely to be the noblest hearts, or even the strongest arms that prevail.
Keywords: Imaginary wars and battles -- Fiction; Fantasy fiction